Romance, reverence, research, rights: Writing about elephant hunting and management in southern Africa, c.1830s to 2008 - Jane Carruthers (Koedoe: African Protected Area Conservation and Science, 2010)
The protection and management of large mammals in Africa’s national parks is not a matter to be left solely for the attention of natural science and scientists. The way in which the natural world is conceptualised by the humanities and social sciences is also significant, because nature is cultural as well as scientific. This article is an interdisciplinary appraisal of the manner in which the writing (e.g. discourse, vocabulary) about elephants in various literary and scientific texts has altered over time. It aims to provide an analysis of some of the literature about elephants in order to examine literate society’s changing responses to the hunting and management of elephants in southern Africa over the past two centuries. The review suggests that new research questions regarding animal cognition and empathy have been generated by these changing attitudes, in conjunction with fresh directions in ecological understanding. Conservation implications: Biodiversity conservation is an inexact science, and even the distinction between conservation research and conservation management is not clear-cut. Moreover, a degree of emotion is evident in scientific and popular discussions around what should be ‘saved’ and how best this might be achieved. Nature is cultural as well as scientific and interdisciplinary insights from the humanities and social sciences may beneficially inform protected area management.